21ST CENTURY EMERGING LEADERSHIP COMPETENCIES IN MALAYSIAN HIGHER LEARNING INSTITUTIONS - TONG WOOI, Chow; HAFEEZ SIDDIQUI, Sulaman; ABDUL JABBAR, Hijattulah; SHAHID NAWAZ, Muhammad (Studia Universitatis Babeș-Bolyai Negotia, 2019)
Purpose: This paper explores the 21st-century emerging leadership competencies in a Malaysian higher learning institution. As the forces of change are transforming the leadership landscape, new leadership capabilities are required for the 21st-century evolving globalized environment. Hence, research is needed to determine the key emerging leadership competencies in the higher learning institutions. Findings: The significance of the results were the relevance of the leadership competency concept in the context of higher learning institution, future leaders need competencies for effective leadership, and the core competencies of academic leaders are necessary. Additionally, besides the discussion on the emerging leadership competencies of visioning and strategic thinking, leadership agility, adaptability and change, relationship and collaboration, the new findings from the field data were corporate leadership and cross-cultural competence. Research limitations/implications: This qualitative case study focused on one higher learning institution. At the same time the research also provided the in-depth context-rich information. Practical implications: The knowledge and adoption of the emerging leadership competencies concept would enhance the development of progressive leadership. Originality/value: There is limited study on the emerging leadership competencies in the higher learning institutions. Hence, there is value in this research. The findings were original contributions to knowledge. Also, this study showed the link between the expected attributes of institutional leadership to the dimensions of transformational leadership and the key emerging leadership competencies. JEL Classification: L290